Information control problems in manufacturing technology 1982 : proceedings of the 4th IFAC/IFIP symposium, Maryland, USA, 26-28 October 1982 - Hardt, D. E. (David E.) (IFAC proceedings series., 1983)
Information Control Problems in Manufacturing Technology 1982 documents the proceedings of the 4th IFAC/IFIP Symposium held in Maryland, USA, on 26-28 October 1982. The volume contains 27 papers divided into six sections. The papers in Section 1 cover the various US government programs sponsoring manufacturing-related research. This support ranges from basic process physics research to general questions of artificial intelligence in the manufacturing environment. At the heart of any manufacturing operation are the unit processes. Proper control of these processes is vital to achieving the autonomy that will eventually lead to automated manufacturing systems. Section 2 addresses these issues in terms of the general control problem involved and in the solution of specific processing problems.